Imaging of Pulmonary Manifestations in Chronic Kidney Disease: A Review - Das, Abanti; Naranje, Priyanka; Bhalla, Ashu Seith; Das, Chandan J. (Indographics, 2023)
Lungs and kidneys share a symbiotic relationship in maintaining homeostasis of body. Hence, derangement of one system is bound to affect the functioning of the other. The thoracic manifestations of chronic renal failure present a wide spectrum ranging from problems related to fluid and salt balance, calcium–phosphate metabolism, compromised immunity, and additional issues related to different modes of dialysis. In most of the cases, chest radiograph coupled with ultrasound and computed tomography (CT) are sufficient to offer a definitive diagnosis. This review aims to summarize the imaging features of thoracic manifestations of chronic kidney disease (CKD) with emphasis on imaging-based discriminating features.
Keywords: chronic kidney disease; pulmonary; pulmonary edema; chest radiograph; CT; pulmonary infection